Geometria sona Reflexoes sobre uma tradicao de desenho em povos da africa ao sul do equador - GERDES, Paulus (Maputo, 1993)
Reflexoes sobre uma tradicao de desenho em povos da africa ao sul do equador
Keywords: Geometria